Analysis of reinforced concrete coupled structural walls via the Beam-Truss Model. (1st October 2020) - Álvarez, Rodolfo; Restrepo, José I.; Panagiotou, Marios; Godínez, Sergio E.
Highlights: The Beam Truss Model is validated for analysis of RC coupled walls. To enhance the capabilities of the BTM is considered bond-slip and dowel action. Force – Displacement response of RC coupled walls is well captured by the EBTM. The EBTM can capture sliding shear failures in coupling beams. The leading pier carries most of the base shear in the coupled walls. Abstract: The use of an enhanced version of the Beam-Truss Model proposed in a previous study to compute the nonlinear response of reinforced concrete coupled walls is discussed in this paper. The results of the cyclic tests of two seven-story one-quarter scale coupled walls tested in New Zealand are used for model validation. Except for the coupling beams, the specimens were identical. One of the specimens (Wall A) had a conventional arrangement of reinforcement in the coupling beams, whereas the other (Wall B) had beams with diagonal bars. Specimen Wall A showed lateral force–displacement response degradation after reaching a 1.6% roof drift ratio. The degradation in specimen Wall A was due to sliding shear of the beams. Specimen Wall B exhibited stable hysteretic response throughout the test. The authors use two kinds of Beam-Truss Models and compare computed and measured key responses in these tests. Computed responses, measured and not measured in the tests, are also compared with the results of Nonlinear Truss Models reported in the literature. This paper shows that the relatively simple and computational-efficient Beam-Truss Models predicted well important aspects of the response, such as the lateral force–displacement envelope, the sliding shear of the coupling beams in specimen Wall A and the ductile behavior of specimen Wall B.